1997
DOI: 10.1080/00288233.1997.9513261
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lime on yield, N fixation, and plant N uptake from the soil by pasture on 3 contrasting trials in New Zealand

Abstract: The amount of plant nitrogen (N) uptake from the soil and fixed N in the herbage of clover species were measured using a 15 N dilution technique on mowing trials at 3 lime rates (0, 5000, and 10 000 kg/ha) at a low rainfall site (Matapiro soil) near Hastings over 5 years and at a high rainfall site (Mangatea soil) near Te Kuiti over 4 years. At the low rainfall site, measurements were also made over 5 years on a grazing trial at 2 lime rates (0, 7500 kg/ha). The dominant clover species was subterranean clover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…Liming, due to the creation of the favourable conditions for the mineralization of organic matter, conditioned the increased content of the nitrogen mineral forms 334 B. Sikiric et al / Span J Agric Res (2011) 9(1), 329-337 in the soil. Therefore, the highest increase of both NH 4 + and NO 3 -was noted in the treatment with the highest lime rate (9 t ha -1 ) (Wheeler et al, 1997). The highest values of mineral nitrogen in the soil were noted in the second year of the experiment, when the effect of liming reached full-scale.…”
Section: Discussionmentioning
confidence: 79%
“…Liming, due to the creation of the favourable conditions for the mineralization of organic matter, conditioned the increased content of the nitrogen mineral forms 334 B. Sikiric et al / Span J Agric Res (2011) 9(1), 329-337 in the soil. Therefore, the highest increase of both NH 4 + and NO 3 -was noted in the treatment with the highest lime rate (9 t ha -1 ) (Wheeler et al, 1997). The highest values of mineral nitrogen in the soil were noted in the second year of the experiment, when the effect of liming reached full-scale.…”
Section: Discussionmentioning
confidence: 79%
“…Addition of lime at 7.5 t ha −1 (Edmeades et al 1986) to a white clover-ryegrass pasture or 5-10 t ha −1 to a sub-clover-ryegrass pasture (Wheeler et al 1997) had no effect on DM, symbiotic dependence or N fixed by the clover (Table 10). Addition of lime at 5-10 t ha −1 to a white clover-ryegrass pasture (Wheeler et al 1997) did not affect legume symbiotic dependence, but fixed N was significantly higher at 5 t ha −1 lime due to an increase in clover DM (Table 10).…”
Section: Aciditymentioning
confidence: 85%
“…Broadcasting lime will ameliorate acidity in the surface soil, but subsoil acidity will remain to the possible detriment of plant growth. The effect of lime addition to acid soils on legume symbiotic performance has been studied predominately in clover-based pastures in the southern hemisphere, including New Zealand (Edmeades et al 1986;Wheeler et al 1997), Australia (Butler 1993;Peoples et al 1995Peoples et al , 1998Unkovich et al 1996) and…”
Section: Aciditymentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al (2004) had reported that acid soils limit microbial growth. However, most experiments in which pH has been manipulated by either acid or lime addition have been relatively short term, and so the soil microbial biomass (SMB) may not have had time to adjust to the radically altered conditions (Wheeler et al, 1997;Curtin et al, 1998). In many soils, lime application has the consequence of solubilizing organic matter.…”
Section: Mbc and Mbn During Maize Growth As Affected By Treatment Appmentioning
confidence: 99%